Biomass to biodegradable polymer (PLA) - Singhvi, Mamata; Gokhale, Digambar V. (RSC Advances, 2013)
Lignocellulosic biomass is renewable and cheap, and it has the potential to displace fossil fuels for the production of fuels and chemicals. Biomass derived lactic acid is an important compound that can be used as a chemical platform for the production of a variety of important chemicals on a large scale. The quality of the monomers of lactic acid and lactide, as well as the chemical changes induced during polymerization and processing, are crucial parameters for controlling the properties of the resulting polylactic acid (PLA) products. In this review, we outline the process of exploiting biomass for the production of polylactic acid, a biodegradable polymer which is well-known as a sustainable bioplastic material.

Biocatalyst development for lactic acid production at acidic pH using inter-generic protoplast fusion - Singhvi, Mamata; Gurjar, Gayatri; Gupta, Vidya; Gokhale, Digambar V. (RSC Advances, 2015)
Global warming and environmental problems force us to develop sustainable processes based on the use of biocatalysts that are eco-friendly with the least potential toxicity. Lactic acid fermentation at neutral pH generates a large amount of gypsum during down-stream processing. Hence it is essential to develop Lactobacillus strains which produce lactic acid at acidic pH thus making the whole downstream process environmentally friendly. Fusant F3 was generated using protoplast fusion between Lactobacillus delbrueckii Mut Uc-3 and Acetobacter pasteurianus NCIM 2314 on solid media at pH 4.0. Fusant F3 was further treated by UV irradiation to generate a mutant, FM1, with improvements in acid tolerance which produced five-fold more lactic acid than the parent strain at acidic pH. The molecular studies using RAPD markers demonstrated that the fusant is derived from both the parental strains, Acetobacter and Lactobacillus and the mutant is derived from the fusant. The utilization of such acid tolerant strains could be able to produce free lactic acid at acidic pH without using neutralizing agents and will offer an effective means for designing environmentally benign processes for lactic acid production.